Effect of Airfoil Profile Variations on the Rear Wing of a Racing Car on the Downforce Coefficient Using Computational Fluid Dynamics (CFD) Simulation - Carlen Muhammad Hendra; Delima Yanti Sari; Arwizet K; Fitrah Qalbina (Unversitas Negeri Padang, 2025)
Variation of airfoil profile shape in race car rear wings plays a crucial role in generating optimal downforce to improve traction and vehicle stability. The main issue addressed in this study is the lack of clarity regarding which airfoil profile and angle of attack configuration are most effective in producing the highest downforce coefficient (Cdown). This research aims to analyze the aerodynamic performance of symmetric airfoils NACA 0012 and NACA 0015 at three different angles of attack, namely 9.5°, 19.5°, and 29.5°, using Computational Fluid Dynamics (CFD) simulation. The simulations were performed under steady-state flow conditions with an appropriate turbulence model to accurately capture pressure distribution and airflow characteristics. Results show that NACA 0012 generated higher and more stable Cdown values at low to medium angles, with the highest value of 1.4 at 29.5°. In contrast, NACA 0015 exhibited a more gradual performance increase and reached a Cdown of 1.2 only at the highest angle. The study concludes that slender airfoil profiles like NACA 0012 are more suitable for circuits with sharp corners, while NACA 0015 is better suited for straight tracks requiring progressive aerodynamic stability. This research contributes to optimizing rear wing design based on the aerodynamic demands of race cars.